Permian plant macrofossils from Fossilryggen, Vestfjella, Dronning Maud Land - McLoughlin, S; Larsson, Kent; Lindström, Sofie (Antarctic Science, 2005)
A low diversity plant macrofossil assemblage described from the northern section of Fossiryggen, Vestfiella, Dronning Maud Land, Antarctica, is dominated by matted leaf impressions of Glossopteris sp. cf. G communis Feistmantel and Glossopteris sp. cf. G spatulata Pant A Singh, and in situ finely branched Vertebraria indica Royle rootlets. Equisetalean stems, rhizomes and leaf whorls (Pkyllotheca australis Brongniart emend. Townrow), isolated seeds, scale-leaves, and fragmentary gymnosperm axes represent minor components of the assemblage. The fossils are preserved in fine-grained, floodbasin sediments and dark palaeosols. Although lacking definitive biostratigraphical indices, the flora is considered to represent a Middle Permian assemblage based principally on lithological and palynological correlation with the southern section at Fossilryggen and broad similarities to mid-Permian plant assemblages elsewhere in Gondwana.